Bimanual control strategies. Issue 4 (April 2019) - Wang, Chaoyi; Shea, Charles H
Two tasks (A and B) were designed which required participants to sequentially move through four target positions in a Lissajous display. Task A was designed so that participants could complete the task using either unimanual or bimanual control strategies. Task B was designed so that participants could complete the task using relatively simple or more complex bimanual control strategies. The purpose of this study was to determine which control strategy the participant utilises to complete the two tasks when Lissajous displays are provided and to determine the degree to which the size of the targets influences the control strategy chosen under these conditions. The movement amplitude between two adjacent targets and the target size resulted in an Index of Difficulty (ID) of 2 and 4 for each task. For both tasks, participants practised 15 trials (30 s per trial) for each ID and then was administered a test trial. The results for both Tasks A and B indicated that the ID2 condition resulted in a circular path, whereas the ID4 condition resulted in a straight-line path on the Lissajous plot. This suggests that at the low ID condition participants produced a continuous 1:1 with 90° phase offset bimanual coordination pattern. At the high ID condition, the participants consistently chose to switch to a more stable unimanual left and right movements in Task A and to transition between in-phase and anti-phase bimanual coordination patterns in Task B. In addition, both limbs' movements were more harmonic in the low ID condition than in the high ID condition.